A Synthesis - Plott, Charles R.; Sunder, Shyam (Journal of Accounting Research, 1981)
Charles R. Plott, Shyam Sunder, A Synthesis, Journal of Accounting Research, Vol. 19, Studies on Standardization of Accounting Practices: An Assessment of Alternative Institutional Arrangements (1981), pp. 227-239